Fast ISAR imaging method for complex manoeuvring target based on local polynomial transform‐fast chirp Fourier transform - Fengkai Liu; Cunqian Feng; Darong Huang; Xinrong Guo (IET Radar, Sonar & Navigation, 2021)
Abstract In ISAR imaging, echo signals of complex manoeuvring targets have to be modelled as multi‐component cubic phase signals (m‐CPS). In this condition, the Doppler diffusion will seriously affect the quality of ISAR imaging. Herein, a complex manoeuvring target imaging method based on local polynomial transform‐fast chirp Fourier transform (LPT‐FCFT) is proposed. In this method, the instantaneous frequency and the quadratic chirp rate of the echo signal are estimated by local polynomial transformation, then the chirp rate and the amplitude are estimated by fast chirp Fourier transform, and finally the high‐resolution ISAR image of the complex manoeuvring target is obtained by CLEAN technology. Compared with the traditional method, the proposed method has the advantages of less computational complexity, clearer imaging results and better anti‐noise performance. Simulation results indicate the effectiveness and superiority of the proposed method.